Differentiation of groups of patients with cognitive complaints at breast cancer diagnosis: Results from a sub‐study of the French CANTO cohort. Issue 4 (31st October 2020) - Hardy‐Leger, Isabelle; Charles, Cécile; Lange, Marie; Joly, Florence; Roux, Pauline; Capel, Aurélie; Petrucci, Jean; Rigal, Olivier; Le Fel, Johan; Vanlemmens, Laurence; Everhard, Sibille; Martin, Anne‐Laure; et al.
Abstract: Objective: Cognitive complaints are more frequent in women with breast cancer (BC) than in healthy controls and can be present before any treatment. Findings regarding contributive factors remain inconsistent. This study aimed to identify different groups of patients with cognitive complaints at BC diagnosis and to determine whether these different groups were associated with demographic, medical, or psychological characteristics. Methods: Cognitive complaints were assessed in a subset of 264 women from the French multicenter prospective CANTO cohort, at baseline before any treatment. Clustering analyzes were performed using the six‐cognitive dimension Costa's scoring of the FACT‐Cog V3. Univariable analyses were used to study how cognitive function (standardized neuropsychological tests, ICCTF), anxiety, depression, fatigue, and quality of life (HADS, FA12, QLQ‐C30) were associated with specific cognitive complaints groups. Results: Results included 263 women (54±11 years), newly diagnosed with BC (69% stages I–III). Four distinct groups emerged, ranged from "no complaints" (22.8%), "low complaints" (55.1), "mixed complaints" (14.5%), to "consistent complaints" (7.6%). No significant differences were found in terms of demographic and medical factors between the four groups. However, the groups with higher proportions of patients with complaints were found to have more impairment in executive function, higher scores of anxiety, depressive symptoms, and fatigue, and lower quality of life, than the groups with lower proportions of cognitive complaints. Conclusion: Using complete cognitive assessment prior to BC treatment, we identified four distinct cognitive complaints groups with specific characteristics. This work provides valuable clinical basis to further investigations for a better understanding of cognitive complaints and their associates.